The halal trade war - Bakar, Normizan; Rawi, Shamsul Bahrain; Hasan Basri, Bakti; Zainol, Zairy; Abd. Wahab, Norazlina; Omar, Hamimi (2014)
This paper analyzes the strategic halal policy where the duopoly firms invest into the halal certification under their governments’ subsidization policies.We analyze the firms’ halal level-price choices and the governments’ optimal halal certification investment policies. The analysis is based on third-country model that is modeled in three-stage game. In the first stage the governments determine an optimal policy and in the following stages the firms first compete in halal certification level and then export to an imperfectly competitive third-market. The study shows, among others, that the governments’ optimal halal certification policy, subsidy or tax, depends on the degree of firms’ halal-price competition